Implimentasi Budaya Gotong Royong Dalam Mewujudkan Nilai-Nilai Pancasila Guna Menerapkan Kehidupan Bermasyarakat - Ainiyah, Nur; Soesanto, Edy; Anjani, Sheira Putri (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Pancasila, as the foundation of the Indonesian state, reflects universal principles such as justice, unity and social welfare. However, to realize Pancasila as a profile that is lived by society, it is necessary to implement a strong culture of mutual cooperation. The culture of mutual cooperation can be implemented in an effective method to increase understanding and application of Pancasila principles in society. In implementing the culture of mutual cooperation in creating the image of Pancasila at Villa Bekasi Indah 2 Housing, research found that the culture of mutual cooperation is still maintained and plays an important role in realizing the principles of Pancasila such as God, Humanity, Unity, Kinship and Social Justice. An effective implementation model involves active participation from all components of society, be it government, non-government organizations, or individuals. In this context, the implementation of mutual cooperation culture is a means of increasing the existence of Pancasila principles in people's daily lives. In the Villa Bekasi Indah 2 housing complex, the culture of mutual cooperation is the basis for establishing harmonious social relations, helping each other in building and maintaining the environment, and plays an important role in supporting social resilience and shared prosperity. Through the implementation of the culture of mutual cooperation, the people of Villa Bekasi Indah 2 can internalize the practice of Pancasila values in their daily activities.